Analisis Pelaksanaan Pembelajaran Daring IPA Materi Magnet Melalui Aplikasi Google Classroom Pada Kelas 6 SDN Tenggilis Mejoyo 1 Surabaya - Muhammad Ihwan Firdaus; Bahauddin Azmy; Susi Hermin Rusminati (Jurnal Literasi Digital, 2021)
Online learning certainly demands the readiness of educators and students. Online learning also really needs technology that can simplify the learning process. With increasingly advanced technology, it is hoped that the world of education affected by this pandemic can develop more and make good use of technology. The current method that can be used is by learning online using the google classroom application. This research aims to describe the online learning process through the online application google classroom science material magnetic material The type of research used is a qualitative approach. In data collection techniques using the method of observation, interviews, and documentation. Data analysis in this study used flow model data analysis by Miles and Huberman. This study concludes that learning magnetic material online through the google classroom application in class VI SDN Tenggilis Mejoyo 1 Surabaya, namely learning magnetic material online through the google classroom application is still lacking even though the teacher has implemented this online learning process properly and in detail. as an effort to carry out online learning in order to create a smooth and effective learning process. However, the role of parents in motivating their children is very necessary so that students are active in online learning through the google classroom application, so that the online learning process can achieve satisfactory assessment criteria and become a reference in future online google classroom learning.